Hubungan VO2Max dengan Resiko Cedera pada Pemain Voli Amatir di Klub Bola Voli Jakarta - Agustiyawan Agustiyawan; Rena Mailani; Fidyatul Nazhira; Ailsa Nahda Ahnafa Amsah; Aby Bima Kesuma (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to identify the relationship between VO2Max and risk of injury among volleyball playersMethods: this study used  a cross-sectional study on 26 male amateur volleyball players method with aged 15 – 18 years. VO2Max was recorded by cooper test and risk of injury was measured by Functional Movement Screen (FMS) Test.Results:  the result obtained that there is relationship the VO2Max and risk of injuries (p = 0.001). A negative  correlation was recorded between the VO2Max and risk of injuries (r = -0.723). Conclusion:  The concluded that there is a relationship between VO2Max and risk of injury on amateur volley players with  a negative correlation.